2020
DOI: 10.1007/s00345-020-03168-1
|View full text |Cite
|
Sign up to set email alerts
|

Robot-assisted simple prostatectomy versus open simple prostatectomy: a single-center comparison

Abstract: Purpose Open simple prostatectomy (OSP) is a standard surgical technique for patients with benign prostatic hyperplasia with prostate size larger than 80 ml. As a minimally invasive approach, robot-assisted simple prostatectomy (RASP) emerged as a feasible surgical alternative. Currently, there are no definite recommendations for the standard use of RASP. Therefore, we aimed at investigating various clinical outcomes comparing RASP with OSP. Methods In this retrospective single-center study, we evaluated clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 27 publications
1
23
0
7
Order By: Relevance
“…LOS data were reported in six studies involving 3,699 patients ( Figure 2B ) ( 5 , 10 , 12 15 ), of whom 936 underwent RASP and 2,763 underwent OSP. Patients treated with RASP had a shorter LOS.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…LOS data were reported in six studies involving 3,699 patients ( Figure 2B ) ( 5 , 10 , 12 15 ), of whom 936 underwent RASP and 2,763 underwent OSP. Patients treated with RASP had a shorter LOS.…”
Section: Resultsmentioning
confidence: 99%
“…Data on EBL were obtained from five studies ( 5 , 10 13 ) including 444 patients (232 in the RASP group and 212 in the OSP group) ( Figure 3A ). The pooled outcome indicated that EBL was lower in the RASP group than in the OSP group (WMD, −304.68; 95% CI, −432.91, −176.44; P < 0.001; I 2 = 86%).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations